ANALYSIS OF REMANDED AND SENTENCED INMATES ON THE BASIS OF AGGRESSION, DEPRESSION, AND ABILITY CHANGES - Devi Mariamdaram Chethiyar, Saralah (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the research was to understand the relationship between aggression, depression, and ability changes. Another objective was to identify the differences between levels of aggression, depression, and ability change in remanded and punished inmates. The Aggression Questionnaire, Beck Depression Inventory, and University of Rhode Island Changes Assessment were applied as core tools to understand inmate’s aggression, depression, and ability changes. The employed research methodology was quantitative. A survey method was used for data collection from 140 young prison inmates in a prison in north Malaysia. The analysis of Levene’s test for equality of variances and t-test for equality of means showed significant differences in aggression, depression, and ability change between remanded and sentenced inmates. Results of the study have shown a significant difference between aggression, depression, and ability change among remanded and sentenced inmates.